Reference to Grammatical Cohesion in the Novel "Konspirasi Alam Semesta" by Fiersa Besari: A Discourse Perspective - Azis, Abd.; Hodairiyah, Hodairiyah; Nurhayati, E.A.A. (Electronic Journal of Education, Social Economics and Technology, 2025)
This study aims to describe the forms of referents as grammatical cohesion contained in a novel by Fiersa Besari in which there are many uses of grammatical cohesion in the form of references. The data source in this study is in the form of novel texts with data obtained in the form of lingual word units. The data collection technique of this research is using the non-involvement of notes (SBLC) method and is followed up with a number of advanced techniques, namely reading, marking, recording, and classification.  Then, the data analysis used is the Agih method with the basic technique for direct elements (BUL) and the advanced technique of the sink technique. The results of the study show that there are three forms of reference to grammatical cohesion in the novel, namely: persona reference (pronoun), demonstrative reference (designation word) and comparative reference (comparative word). The three references have relationships between sentences, the use of references cannot be moved or eliminated in the sentence so that the sentence or novel text has a cohesive and understood meaning. However, if the reference is removed, the sentence cannot be understood and contains a vague meaning.